No to cookies: Empowering impact of technical and legal knowledge on rejecting tracking cookies. (July 2021) - Strycharz, Joanna; Smit, Edith; Helberger, Natali; van Noort, Guda
Abstract: The General Data Protection Regulation (GDPR) introduced in 2018 in the EU aims to give consumers a high degree of control over their data online in order to allow them to protect their privacy. It also puts high transparency requirements for websites that collect and process data. In fact, consumers have to be informed about technical and legal aspects of data collection; this knowledge should empower them to consciously give or withdraw their consent for data collection. The current study investigates the empowering impact of technical and legal knowledge about online data collection within the theoretical framework of the Protection Motivation Theory, the Regulatory Focus Theory, and contextual integrity. An online experiment in which participants are exposed to a technical or legal knowledge intervention in either commercial or news website context shows that receiving both kinds of information leads to lower threat appraisal. At the same time, having legal knowledge empowers consumers: it positively impacts their coping appraisal and motivation to reject online data collection. The study findings raise questions about the current transparency requirements about data collection and highlight the importance of legal knowledge as well as law enforcement for online privacy protection of consumers. Highlights: Receiving technical and legal knowledge intervention does not increase individuals' motivation to reject tracking cookies. Receiving technical or legal knowledge intervention lowers individuals' threat perceptions of online data collection. Higher levels of legal knowledge increase individuals' coping appraisal and motivation to reject tracking cookies. Not coping and threat appraisal, but privacy concern and attitude toward personalization impact motivation to reject cookies.